Hairy kisses: tactile cheliceral courtship affects female mating decisions in Leucauge mariana (Araneae, Tetragnathidae) - Aisenberg Olivera, Anita (2015)
Sexual selection is thought to be an important force driving the evolution of sexually dimorphic morphology and behavior, but direct experimental tests of the functions of species-specific details of morphology are rare and usually incomplete. The males of most species of the large spider family Tetragnathidae possess large sexually dimorphic che- licerae that are used when the sexes lock together before and during mating. In Leucauge mariana, the female’s chelicerae clasp those of the male; mating does not begin until the female’s chelicerae seize the male and does not end until they release him. In addition, females contribute material to formç genital plugs in the female’s genitalia. Male chelicerae have sexually dimorphic and species-specific setae and ledges in areas that contact the female during cheliceral clasps. We tested the hypothesis that stimuli from these structures trigger mating processes that are controlled by the female which could increase male reproductive success. We reduced or eliminated possible stimulation of the female in two ways: removing male cheliceral setae that contact the female, and removing setae on the female’s chelicerae and endites that are contacted by and could thus be stimulated by the male’s chelicerae and their setae. Both male and female modifications had similar effects that likely reduced the male’s chances of paternity: female receptivity to re-mating increased, copulatory plug formation decreased, and interruptions during copulation became more frequent. As expected under the stimulation hypothesis, blocking female sensory abilities generally had greater effects on these responses than modifying male stimulatory structures.